PENGATURAN PERIZINAN TOKO SWALAYAN SEBAGAI POTENSI PENDUKUNG KEPARIWISATAAN DI BALI - Suantra, I Nengah; Nurmawati, Made; Suka Asih K TUS, Desyanti (Institut Hindu Dharma Negeri Denpasar, 2018)
In Bali, quota of supermarkets are exceed and many are unlicensed. The purposes of this normative legal research are to analyze the issuance of the licenses and the existence of the illegal supermarkets. Research on the primary legal materials, secondary legal materials and tertiary legal materials are using statutory approach and conceptual approach. The legal materials are includes interview with the authority in the Law and Human Rights department, Trade Department, and Tourism Department in Kabupaten Tabanan, Badung, Klungkung and Kota Denpasar; inventoried, identified, interpreted, then presented in analytically descriptive. The regulation of supermarkets performed with local regulation, regent or mayor regulation, and mayor decree. However there are areas which have no regulation for supermarkets. The unlicensed supermarkets are more than the licensed supermarket. The unlicensed supermarkets allowed to operate the business because the licenses are in process, do not turn off businesses, and do not increase unemployment. However, it is developed, and who is disobey provided a written warning, some even close. Supermarkets are strongly support tourism because it is easy to find, easy to get the goods needed with more guaranteed quality, shop comfortably, safely and have certainty of price. The regulation of supermarkets are more precise with local regulation.